If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -17 = -4x + 3 Reorder the terms: -17 = 3 + -4x Solving -17 = 3 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -17 + 4x = 3 + -4x + 4x Combine like terms: -4x + 4x = 0 -17 + 4x = 3 + 0 -17 + 4x = 3 Add '17' to each side of the equation. -17 + 17 + 4x = 3 + 17 Combine like terms: -17 + 17 = 0 0 + 4x = 3 + 17 4x = 3 + 17 Combine like terms: 3 + 17 = 20 4x = 20 Divide each side by '4'. x = 5 Simplifying x = 5
| 11-7(12k+2)=-(3-4k)-3k | | 2g+3(-7+2g)=1-9 | | .50x+.35(70)=44.5 | | 125+13x=21 | | -2y+6=y^2-9 | | 5(2)+2=10 | | -(3x+3)-2(3y+3)= | | 7a^3+22a^2+3a=0 | | 7(5x-2)=7(4x+6) | | x(9)=54 | | -x-2=12x | | 6n-5n+4n=20 | | -6a-6a=24 | | 2(x+8)-6x=-2(x-3) | | 1.4(z+0.5)=0.7(z-1.3) | | -2-13.8n=-8-(6n+1) | | -4y-16=2x | | 15=3over | | m+11=1 | | -11y+32=104-5t | | 90+90+x+x+x+x=180 | | 12.3=9.4+a | | 26=pi*d | | -6.6x+11+1.3+2x= | | -14+s=6 | | 2(2k*1)=4(k*2) | | 3x+18=5x+20 | | -5(7p-1)-(1+2p)=3+8p+1 | | -11+r=5 | | 8x-2x+5x= | | 4a+2a-3a=9 | | 13b-39=2 |